PIL ANTI HAID UNTUK IBADAH PERSPEKTIF HUKUM ISLAM - Aminullah, Amiruddin (Jurnal Pendidikan Kreatif, 2023)
Menstruation is a biological process that signifies sexual maturity in women and is associated with Shariah rules in worship. A woman who has experienced menstruation is considered to have reached the stage of adulthood or "baligh" according to Islamic law. While menstruation is natural, there's controversy surrounding the use of menstruation-delaying drugs to facilitate religious obligations such as fasting or pilgrimage. Some scholars and institutions like the MUI believe that using these drugs for worship purposes is mubah or permissible, provided it doesn't have negative health implications. However, using these drugs for other reasons, especially those that go against religious norms, is deemed forbidden.